2000
DOI: 10.1007/s002689910116
|View full text |Cite
|
Sign up to set email alerts
|

Hypomagnesemia and Hypocalcemia after Thyroidectomy: Prospective Study

Abstract: Hypomagnesemia after total thyroidectomy has not been studied extensively. Our anecdotal experience suggests that it may be important in some patients after thyroid excision. The hypomagnesemic hypocalcemic syndrome has been described in other disease states in which a state of functional hypoparathyroidism exists. This study was designed to determine the incidence of hypomagnesemia after total thyroidectomy and relate it to hypocalcemia and symptoms during the postoperative period. A prospective study of all … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
108
4
7

Year Published

2002
2002
2013
2013

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 131 publications
(124 citation statements)
references
References 32 publications
5
108
4
7
Order By: Relevance
“…In our study, the rate of the patients with laboratory transient hypocalcemia (27%) and those with clinically transient hypocalcemia (23%) was in the interval of 6.2-68%, which was simi-lar to that reported in the literature. 2,3,14,[22][23][24][25][26] In the study by Wilson et al, in which the definitions of laboratory and clinical hypocalcemia are similar to the definitions in our study, 68% of patients were diagnosed with laboratory transient hypocalcemia and 36% of patients had symptoms of hypocalcemia. 3 They defined hypomagnesemia as serum concentration of magnesium lower than 0.7 mmol/L and the same definition was used in our study.…”
Section: Discussionmentioning
confidence: 74%
See 3 more Smart Citations
“…In our study, the rate of the patients with laboratory transient hypocalcemia (27%) and those with clinically transient hypocalcemia (23%) was in the interval of 6.2-68%, which was simi-lar to that reported in the literature. 2,3,14,[22][23][24][25][26] In the study by Wilson et al, in which the definitions of laboratory and clinical hypocalcemia are similar to the definitions in our study, 68% of patients were diagnosed with laboratory transient hypocalcemia and 36% of patients had symptoms of hypocalcemia. 3 They defined hypomagnesemia as serum concentration of magnesium lower than 0.7 mmol/L and the same definition was used in our study.…”
Section: Discussionmentioning
confidence: 74%
“…2,3,14,[22][23][24][25][26] In the study by Wilson et al, in which the definitions of laboratory and clinical hypocalcemia are similar to the definitions in our study, 68% of patients were diagnosed with laboratory transient hypocalcemia and 36% of patients had symptoms of hypocalcemia. 3 They defined hypomagnesemia as serum concentration of magnesium lower than 0.7 mmol/L and the same definition was used in our study. They reported that the incidence of postoperative hypomagnesemia was considerably higher (72%) than that in our patients who did not receive infusion of magnesium sulphate (2/24 patients, i.e 8%).…”
Section: Discussionmentioning
confidence: 74%
See 2 more Smart Citations
“…Plasma calcium correction without concurrent normalization of magnesium may prolong the clinical manifestations. 7,10 Temporary hypoparathyroidism leads to a reduction in renal reabsorption of magnesium, and expansion of the extracellular volume increases magnesium excretion. 10 According to Wilson et al, 10 10.0% of patients who undergo total thyroidectomy develop hypomagnesemia and hypocalcemia.…”
Section: Discussionmentioning
confidence: 99%